Ex situ management as insurance against extinction of mammalian megafauna in an uncertain world. Issue 4 (3rd July 2020) - Farhadinia, Mohammad S.; Johnson, Paul J.; Zimmermann, Alexandra; McGowan, Philip J.K.; Meijaard, Erik; Stanley‐Price, Mark; Macdonald, David W.
Abstract: The persistence of endangered species may depend on the fate of a very small number of individual animals. In situ conservation alone may sometimes be insufficient. In these instances, the International Union for Conservation of Nature provides guidelines for ex situ conservation and the Convention on Biological Diversity (CBD) indicates how ex situ management can support the CBD's objectives by providing insurance policies for species. The circumstances that justify its use are uncertain. To evaluate the current in situ extinction risk and ex situ management of 43 critically endangered species of mammalian megafauna, we used nonmetric multidimensional scaling and geopolitical variables related to governance, economics, and national policy within their extant ranges. We then fitted generalized additive models to assess the contribution of each variable to the ordination. Fifteen (almost one‐third) of the world's terrestrial mammalian megafauna are not the subject of any ex situ management. Seventy‐three percent of these taxa occur in areas characterized by political uncertainty, such as border zones or areas affected by armed conflicts, mainly in Africa and the Middle East. A further 23% of taxa in ex situ programs do not meet sustainability criteria for inbreeding avoidance. Strategic conservation planning, such as the One Plan approach, may improve ex situ management for these taxa. Given the escalating trend in threats afflicting megafauna, ex situ management should be considered more rigorously, particularly in politically unstable regions, to achieve CBD Target 12 (prevent extinction of threatened species). Abstract : Article impact statement : One‐third of critically endangered large mammals, most occurring in politically unstable areas, are not supported by ex situ management. Abstract : Manejo Ex Situ como Protección contra la Extinción de la Megafauna de Mamíferos en un Mundo Incierto Resumen: La persistencia de las especies en peligro puede depender del destino de un número muy pequeño de animales individuales. La conservación in situ por sí sola a veces puede ser insuficiente. Bajo estas instancias, la Unión Internacional para la Conservación de la Naturaleza proporciona directrices para la conservación ex situ y la Convención sobre la Diversidad Biológica (CBD) indica cómo el manejo ex situ puede apoyar a lograr sus objetivos al proporcionar políticas de protección para las especies. Las circunstancias que justifican el uso del manejo ex situ son inciertas. Para evaluar el actual riesgo de extinción in situ y el manejo ex situ de 43 especies de megafauna de mamíferos en peligro crítico de extinción usamos un escalamiento multidimensional no métrico, así como variables geopolíticas relacionadas con el gobierno, la economía y las políticas nacionales dentro de la distribución actual de estas especies. Después ajustamos los modelos sumativos generalizados para evaluar la contribución de cada variable a la ordinación. Quince (casi un tercio) de los mamíferos terrestres pertenecientes a la megafauna no están sujetos a ningún tipo de manejo ex situ. El 73% de estos taxones ocurren en áreas conocidas por su incertidumbre política, como zonas fronterizas o áreas afectadas por conflictos armados, principalmente en África y en el Oriente Medio. Además, un 23% de los taxones que sí se encuentran en programas de conservación ex situ no cumplen con los criterios de sustentabilidad para evitar la endogamia. La planeación de la conservación estratégica, como la estrategia de One Plan, podría mejorar el manejo ex situ para estos taxones. Dada la tendencia creciente en las amenazas que afectan a la megafauna, el manejo ex situ debería considerarse de manera más rigurosa, particularmente en las regiones con inestabilidad política, para alcanzar el Objetivo 12 de la CBD (evitar la extinción de especies amenazadas). 摘要: 濒危物种的续存可能取决于该物种极少数个体的命运;因此, 仅仅只有就地保护有时还不足够。在这些情况下, 世界自然保护联盟 (IUCN) 为迁地保护提供了指导方针, 《生物多样性公约 (CBD) 》也指出了迁地管理如何通过为物种提供保险政策来支持 CBD 目标。然而, 应在怎样的情况下合理利用迁地保护仍存在疑问。为了评估43种极度濒危的巨型哺乳动物目前的就地灭绝风险和迁地管理, 我们利用非度量多维标度法和动物现生分布区内与治理、经济和国家政策相关的地理政治变量进行了分析。我们还进一步拟合了广义加性模型以评估各变量对等级排序的贡献。世界陆生巨型哺乳动物中有15种 (近三分之一) 未被纳入任何迁地管理项目之中。这些类群中 73%分布在政治不稳定的地区, 如边境地区或受武装冲突影响的地区, 主要在非洲和中东。迁地保护项目中还有 23%的类群没有满足避免近亲繁殖的可持续性标准。战略保护规划, 如一体计划方案 (One Plan approach), 可以帮助改进这些物种的迁地管理。鉴于巨型动物面临的威胁仍在不断加剧, 为了实现 CBD 目标 12 (防止濒危物种灭绝), 应该更严格地考虑迁地管理, 特别是在政治不稳定的地区。 【翻译:胡怡思;审校:聂永刚】